Effect of high heat treatment on poly unsaturated fatty acid profile of ghee - sen, Munmun (Indian Journal of Dairy Science, 2017)
Ghee is a heterogeneous mixture of complex triglycerides. Hence, there is a direct relationship between chemical composition and physical properties of milk fat. It is a good source of lipid nutrients, fat soluble vitamins etc. During heating various changes occur in fats because at high temperature both thermolytic and oxidative reactions occur simultaneously. Both saturated and unsaturated fatty acids undergo chemical decomposition when exposed to heat in the presence of oxygen. This results in loss of valuable nutrients like essential fatty acids (especially poly unsaturated fatty acids), which are destroyed due to oxidation reactions on the unsaturated bonds. In fresh ghee, total poly-unsaturated fatty acid content was found to be 2.5964%, which was adversely affected by heating at 200áµ’C and decreased from initial level to 2.0962% after 40 min of heating.